A multicenter, randomized, double-blind, placebo-controlled trial evaluating the efficacy and safety of Huangqi Guizhi Wuwutang granule in patients with rheumatoid arthritis. Issue 11 (March 2019) - Wang, Yiru; Liu, Yang; Xi, Zhijie; Yu, Yang; Liu, Li; Mao, Jianchun; Xiao, Lianbo; Gu, Xiaohua; Yao, Min; Cui, Xuejun; Shi, Qi; Wang, Yongjun; et al.
Abstract: Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by swelling, pain, and synovial damage. Effective methods lack in the treatment of RA. A traditional prescription in use for thousands of years in China, Huangqi Guizhi Wuwutang granule (HGWG) is still chosen to relieve pain and prevent joint malformation in RA patients. However, no evidence-based medical research has been organized to assess the effectiveness and safety of HGWG for RA. Methods/design: We will conduct a multicenter, randomized, double-blind, placebo-controlled clinical trial to determine whether HGWG can relieve pain and protect joints. We will randomly divide 120 patients with active RA into 2 groups, treated for 12 weeks. Main measurement is the rate of ACR50 score (American College of Rheumatology) from the baseline to 12 weeks. Secondary measurements include rate of ACR20/70, change of Disease Activity Score (DAS) 28, Health Assessment Questionnaire-Disability Index (HAQ-DI), Patient Assessment of Arthritis Pain, Patient Global Assessment of Arthritis, and AIS score. The time points are set as baseline, 2 weeks, 4 weeks, 8 weeks, 12 weeks, 24 weeks, and 48 weeks. In addition, the rate of ACR50 from the baseline to 2 weeks, 4 weeks, 8 weeks, 24 weeks, and 48 weeks' follow-up are also the secondary outcome measures. Discussion: The findings of this research will elucidate the efficacy and safety of HGWG and provide an alternative treatment for RA. In addition, our data will benefit the clinical decision-making on active RA and possibly be incorporated into future guidelines. Trial registration: ClinicalTrials.gov ID: NCT03593837.